BESARAN DEFISIT ENERGI DAN PROTEIN PADA ANAK USIA SEKOLAH (6-12 TAHUN) UNTUK PERENCANAAN PROGRAM GIZI (PMTAS) DI DELAPAN WILAYAH INDONESIA (Laporan Analisis Lanjut Tahun 2014) - salimar salimar; Budi Setyawati; Anies Irawati (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2016)
Consumption adequacy in school children must be noticed, because of nutritional intake is directly associated with nutritional status of children besides of the infectious disease. The aim of this study was to analyse the proportion and the number of consumption deficit of energy and protein, for planning program of nutrition improvement (complementary food for school children/PMTAS) according to regions in Indonesia. Cross sectional study design. The sample of this study was all of children aged 6-12 years from Riskesdas data in 2010 which had the data of consumption. Data analysis describe the deficit of protein and energy according to groups of age and 8 regions in Indonesia. Proporsion of children who had energy deficit was 83,9 percent nationally, 64,4 percent of children was classified having severe energy deficiency (<70% AKE), and proportion of protein deficit was 64,2 percent, 17,8 percent of children was classified having severe protein deficiency (<70% AKP).  The mean of protein and energy deficit for planning program of nutrition improvement nationally in school children require the adding about 650 calories for energy and 8,1 grams for protein. The number of protein and energy deficit was different according to groups of age and region. Protein adequacy for children in group of 6 years had fulfilled the recommended dietary allowance in 5 regions. The largest number of protein and energy deficit was in children aged 10-12 years in 8 regions of Indonesia. For the program planning of nutrition improvement in school children is supposed to notice the groups of age and regions. Kecukupan konsumsi pada anak sekolah harus diperhatikan, karena intake makanan berhubungan langsung dengan status gizi anak selain infeksi penyakit. Tujuan analisis mengetahui proporsi dan besaran defisit konsumsi energi dan protein, untuk perencanaan program perbaikan gizi (Pemberian Makanan Tambahan Anak Sekolah/PMTAS)  menurut wilayah di Indonesia. Disain penelitian cross sectional. Sampel adalah semua anak berumur 6-12 tahun dari data Riskesda 2010 yang mempunyai data konsumsi makanan. Analisis data memaparkan defisit energi dan protein berdasarkan kelompok umur dan 8 wilayah di Indonesia. Proporsi anak usia sekolah yang defisit energi secara nasional 83,9 persen, sebanyak 64,4 persen defisit energi tergolong berat (<70 % AKE), dan defisit protein sebesar 64,2 persen, sebanyak 17,8 persen defisit protein tergolong berat (<70 % AKP). Rata-rata defisit energi dan protein secara nasional untuk perencanan program perbaikan gizi anak usia sekolah adalah perlu tambahan sebesar 650 Kalori untuk energi dan 8,1 gram untuk protein. Besaran defisit energi dan protein berbeda berdasarkan kelompok umur dan wilayah. Kecukupan protein kelompok umur 6 tahun sudah memenuhi AKP di 5 wilayah. Defisit energi dan protein terbesar terdapat dikelompok umur 10-12 tahun di 8 wilayah Indonesia. Dalam perencanaan program perbaikan gizi anak usia sekolah perlu memperhatikan kelompok umur dan wilayah.